A comparison of R&D indicators for the Vancouver biotechnology cluster (2008)
The basis of this paper is to go beyond abstract defi nitions of what a cluster is, and look at a variety of measurable indicators, to see which can demonstrate the presence of a cluster. The example presented is based on the biotechnology industry in Vancouver, Canada. Biotechnology differs from conventional industries, in that there are few tangible goods or services traded, but rather the basis of value creation is primarily the sale or licensing of intangible intellectual property or the (usually pre-revenue) fi rms themselves. The two main questions we aim to test are (i) is there a biotechnology cluster in Vancouver, and (ii) what are its inputs, outcomes, and impact on the region? We use data provided from local and federal agencies such as LifeSciences British Columbia and Statistics Canada to compare biotechnology R & D activity across regions, and within the local economy. Our fi ndings indicate that there is signifi cant activity around biotechnology R & D and commercialisation in Vancouver, but no guarantee of the longevity of the innovation system.